The Development and Optimization of a Polymer Conformance Control Technology in Mature Reservoirs: Laboratory Experiments vs. Field Scale Simulation - Dang, T. Q. C.; Chen, Z.; Nguyen, T. B. N.; Bae, W.; Chung, T.; Tu, T. N. (Energy sources. Part A, Recovery, utilization, and environmental effects, 2014)
This article presents a successful investigation of polymer gel behavior from laboratory experiments to full field scale simulation. First, a series of laboratory experiments are conducted to achieve a deep understanding of polymer gel behavior. The results show that the polymer viscosity, gelation time, and gel strength strongly depend on the reservoir temperature, polymer type, polymer concentration, cross-linker concentration, pH, and salt concentration, which are the keys of a polymer conformance control process. According to the laboratory experiments, polymer gel flooding is applied for the White Tiger field, which is the biggest oil field in Viet Nam. The polymer gel treatment is simulated in the full field scale and the results indicate that it is an excellent candidate for conformance control. Water production decreases from 4,800 m 3 /d to slightly less than 2,000 m 3 /d, while a significant increase in oil production has been achieved from unswept zones, which is a really successful evidence of the polymer conformance control technology in heterogeneous reservoirs.